Selective membranes in water and wastewater treatment: Role of advanced materials. (November 2021) - Zuo, Kuichang; Wang, Kunpeng; DuChanois, Ryan M.; Fang, Qiyi; Deemer, Eva M.; Huang, Xiaochuan; Xin, Ruikun; Said, Ibrahim A.; He, Ze; Feng, Yuren; Shane Walker, W.; Lou, Jun; et al.
Graphical abstract: Abstract: Membrane separation has enjoyed tremendous advances in relevant material and engineering sciences, making it the fastest growing technology in water treatment. Although membranes as a broad-spectrum physical barrier have great advantages over conventional treatment processes in a myriad of applications, the need for higher selectivity and specificity in membrane separation is rising as we move to target contaminants at trace concentrations and to recover valuable chemicals from wastewater with low energy consumption. In this review, we discuss the drivers, fundamental science, and potential enabling materials for high selectivity membranes, as well as their applications in different water treatment processes. Membrane materials and processes that show promise to achieve high selectivity for water, ions, and small molecules—as well as the mechanisms involved—are highlighted. We further identify practical needs, knowledge gaps, and technological barriers in both material development and process design for high selectivity membrane processes. Finally, we discuss research priorities in the context of existing and future water supply paradigms.